Dimeria mahendragiriensis - A new species of Poaceae from Orissa, India - Ravi, N.; Saxena, H. O.; Brahmam , M. (Rheedea, 1995)
A new species of Dimeria R. Br. viz., D. makendragiriensis, is described and illustrated.